UPAYA MENINGKATKAN HASIL BELAJAR BIOLOGI MELALUI PENERAPAN PEMBELAJARAN TUTOR SEBAYA PADA SISWA KELAS XII IPS5 SMA NEGERI 1 LUWU UTARA - Lalak, Andi (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2019)
This research is a classroom action research (CAR) which aims to improve student biology learning outcomes through the application of the cooperative learning model Peer Tutor. The subjects of this study were students of class XII IPS5 in SMA Negeri 1 Luwu Utara in odd semester 2018/2019 academic year consisting of 30 students. The implementation of this study consisted of two cycles and the collected data was analyzed using quantitative analysis. The results showed that the application of the peer learning cooperative learning model was an effective learning strategy to improve the biology learning outcomes of class XII IPS5 students at North Luwu 1 Public High School. The increase is indicated by the results of research from cycle I to cycle II, namely the average value of student learning outcomes increased from 78.89 to 83.89 and an increase in the percentage of students who completed from 56,67% to 90%.Â Kata Kunci: Learning outcomes, peer tutors